2011
DOI: 10.1089/dna.2010.1079
|View full text |Cite
|
Sign up to set email alerts
|

Study on DNA-Binding and DNA-Cleavage Properties of Cr(III) Complexes with Polypyridyl Ligands

Abstract: Two new water-soluble Cr(III) complexes [Cr(IP)(2)Cl(2)](+) and [Cr(PIP)(2)Cl(2)](+) (IP = imidazo[4,5-f][1,10]phenanthroline, PIP = 2-phenylimidazo[4,5-f][1,10]phenanthroline) were synthesized and characterized by elemental analysis, mass spectra, and ultraviolet-visible spectra. The DNA-binding properties of the two complexes were investigated by spectroscopic methods and viscosity measurements. The results indicate that both complexes bind to DNA via an intercalative mode with moderate strength. The fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Different results might be due to the different electronic effect of N‐H group, which the substituent introduced on the benzene ring complexes 1 and 3 . The results also imply that the cleave ability of these complexes may be mainly through the PHIP and DPPZ ligands . Meanwhile, the electronic effect of hntdtsc or satsc is one of the factors in determining the cleave abilities.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Different results might be due to the different electronic effect of N‐H group, which the substituent introduced on the benzene ring complexes 1 and 3 . The results also imply that the cleave ability of these complexes may be mainly through the PHIP and DPPZ ligands . Meanwhile, the electronic effect of hntdtsc or satsc is one of the factors in determining the cleave abilities.…”
Section: Resultsmentioning
confidence: 94%
“…Our previous results also indicated that upon increasing the appending aromatic moiety, the biological activities of oxidovanadium complexes tend to be better . It seems to us that the introduction of some novel ligands may be a useful tool in moderating the antitumor effects of vanadium complexes . Thus, changes in ligand architectures, such as an appending aromatic moiety substituents were placed onto the 1, 10‐phenanthroline ligand framework, may provide an avenue toward oxidovanadium (IV) complexes for their antitumor effects; such topics are scarcely investigated before.…”
mentioning
confidence: 99%
“…The buffer liquidity time in seconds was recorded as t °. The relative viscosity for DNA in the absence ( η °) and presence ( η ) of the complexes was estimated using the equation η = ( t − t °)/ t °, where t is the recorded fluidity time in seconds and the relative viscosity ( η / η °) was plotted against 1/ R ( R = [DNA]/[metal chelate]) …”
Section: Methodsmentioning
confidence: 99%
“…The value of K b were calculated as well using the equation, reaching (4. 38 ) [28], under our experimental conditions. This may due to the introduction of imidazole ring in auxiliary ligands substituted with 1, 10-phenanthroline, which leads to formation of a richer conjugated armatic structure, thus resulting in stronger insertion into DNA.…”
Section: Electronic Absorption Titrationmentioning
confidence: 95%
“…The enhancement of emission intensity is an indication of binding of the complexes to the hydrophobic pocket of DNA, since the hydrophobic environment inside the DNA helix reduces the accessibility of water molecules to the complex and the complex mobility is restricted at the binding site, leading to decrease of the vibrational modes of relaxation [38]. The fluorescence spectroscopic data shows that 1 interacts with CT-DNA more strongly than both 1 and 2, consistent with the UV-Vis absorption titration spectral results.…”
Section: Fluorescence Spectroscopic Studiesmentioning
confidence: 99%